2016
DOI: 10.15430/jcp.2016.21.4.294
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oral Contraceptive Pills on Increased Risk of Breast Cancer in Iranian Populations: A Meta-analysis

Abstract: BackgroundCancer is one of the main public health issues in the world. Breast cancer is one of the most common types of cancer among women. It is also the second cause of mortality in women. The association between the use of oral contraceptive pills and breast cancer is controversial and a main issue in public health. Some findings have shown that taking these pills does not have a significant effect in increasing the risk of breast cancer, while others have confirmed the carcinogenic effect of these products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 39 publications
2
15
0
6
Order By: Relevance
“…Bethea et al have also shown that the OCP use, especially long-term use, was associated with an increased risk of breast cancer (20). Use of OCPs is associated with increased risk of breast cancer due to the direct elevation of estrogen levels and the role of progesterone in gaining weight indirectly (21). Our study indicated that healthy women in class 1 were also more likely to consume OCP.…”
Section: Discussionsupporting
confidence: 65%
“…Bethea et al have also shown that the OCP use, especially long-term use, was associated with an increased risk of breast cancer (20). Use of OCPs is associated with increased risk of breast cancer due to the direct elevation of estrogen levels and the role of progesterone in gaining weight indirectly (21). Our study indicated that healthy women in class 1 were also more likely to consume OCP.…”
Section: Discussionsupporting
confidence: 65%
“…The results of this study are also in line with the results of research Nissa et al, (2017) which stated that the factors that play a role in the case of breast cancer are exogenous hormonal exposure such as the use of hormonal contraception. Another study that is in line with the results of the above study is the research of Soroush et al, (2016) explained that the use of hormonal contraceptive pill types after more than 4 years can increase the risk of breast cancer 1.52 times.…”
supporting
confidence: 81%
“…It can be said that the oral contraceptives can be a risk factor for the development of breast cancer and there is support for something like this in literature. (24) In this study the results show that more subjects were exposed to the x-ray examination method, mammography. Even 74.0% of respondents were exposed to a certain radiation dose indicating that mammography could be a risk factor for breast cancer, as statistically significant results (p= 0.001, p < 0.05) were obtained.…”
Section: Discussionmentioning
confidence: 68%